Trail guide to the body how to locate muscles, bones and more. Student handbook - Biel, Andrew. (Andrew Biel, 2005)
Introduction; Navigating the body; Shoulder and arm; Forearm and hand; Spine and thorax; Head, neck and face; Pelvis and thigh; Leg and foot